An Analysis of the Influence of Social Media and Digital Platforms on the Islamic Understanding of Generation Alpha - Al Awwali, Sholihin (Faculty of Tarbiyah and Teacher Training, Universitas Islam Negeri Alauddin Makassar, 2025)
The increasing social media consumption among Generation Alpha - the digital-native cohort born after 2010 - has introduced both new opportunities and challenges in the realm of Islamic religious education. This is particularly evident in the context of online learning, an area that remains underexplored empirically at the junior high school level. This study aims to examine the influence of social media and digital platforms on students’ understanding of Islam at Muhammadiyah 1 Berbah Middle School, while also identifying the digital literacy challenges they encounter. Adopting a quantitative descriptive approach, the study involved a sample of 152 students selected through stratified random sampling based on grade level and gender, from a total population of 250 students. Data were collected using a closed-ended questionnaire employing a 4-point Likert scale to assess four key variables: social media usage, understanding of Islamic teachings, digital literacy, and perceived benefits and challenges. Analysis using SPSS revealed that social media plays a dual role: while 63% of respondents reported that it supported their understanding of Islamic teachings, 68% frequently encountered conflicting religious information, and only 55% consistently verified such content. Moreover, 57% of students acknowledged the need for guidance in filtering religious information online. These findings highlight the urgent need for digital literacy training, greater educator involvement, and the development of credible Islamic content to enhance the positive impact of social media on religious education. Further research is recommended to explore causal relationships and the influence of other stakeholders, such as families, in strengthening students’ religious digital literacy. Abstrak: Fenomena meningkatnya konsumsi media sosial oleh Generasi Alfa, generasi digital-native yang lahir setelah tahun 2010, telah membawa tantangan dan peluang baru dalam pendidikan agama Islam, khususnya dalam konteks pembelajaran daring yang belum banyak diteliti secara empiris di tingkat sekolah menengah pertama.Penelitian ini bertujuan untuk menganalisis pengaruh media sosial dan platform digital terhadap pemahaman Islam di kalangan siswa SMP Muhammadiyah 1 Berbah, sekaligus mengidentifikasi tantangan literasi digital yang mereka hadapi. Penelitian ini menggunakan pendekatan deskriptif kuantitatif dengan jumlah sampel 152 siswa yang diambil melalui stratified random sampling berdasarkan jenjang kelas dan jenis kelamin dari total populasi 250 siswa. Instrumen penelitian berupa kuesioner tertutup dengan skala Likert 4 poin untuk mengukur empat variabel: penggunaan media sosial, pemahaman ajaran Islam, literasi digital, serta manfaat dan tantangan yang dirasakan. Hasil analisis data dengan SPSS menunjukkan bahwa media sosial berperan ganda: 63% responden merasa terbantu dalam memahami ajaran Islam, namun 68% sering menemukan informasi keagamaan yang bertentangan dan hanya 55% yang secara konsisten memverifikasi informasi tersebut. Sebanyak 57% mengaku memerlukan panduan dalam memilah informasi agama secara daring. Temuan ini menegaskan pentingnya pelatihan literasi digital, keterlibatan pendidik, serta pengembangan konten keislaman yang kredibel guna mengoptimalkan peran media sosial dalam pendidikan agama. Penelitian lanjutan disarankan untuk mengeksplorasi hubungan kausal dan peran aktor lain seperti keluarga dalam meningkatkan literasi digital keagamaan.